The Efflux Mechanism of Fraxetin-O-Glucuronides in UGT1A9-Transfected HeLa Cells: Identification of Multidrug Resistance-Associated Proteins 3 and 4 (MRP3/4) as the Important Contributors - Qin, Zifei; Zhang, Beibei; Yang, Jing; Li, Shishi; Xu, Jinjin; Yao, Zhihong; Zhang, Xiaojian; Gonzalez, Frank J.; Yao, Xinsheng (Frontiers in Pharmacology, 2019)
Fraxetin, a natural compound present in many dietary supplements and herbs, is useful in the treatment of acute bacillary dysentery and type 2 diabetes. Previously, several metabolic studies have revealed extensive first-pass metabolism causing formation of fraxetin-O-glucuronides (G1 and G2), resulting in poor bioavailability of fraxetin. Active transport processes play an important role in the excretion of fraxetin-O-glucuronides. Nevertheless, the transporters involved are yet to be elucidated. In this study, we aimed to determine the active efflux transporters, including breast cancer resistance protein (BCRP) and multidrug resistance-associated proteins (MRPs), involved in the excretion of fraxetin-O-glucuronides. A chemical inhibitor, MK571 (5 and 20 μM), a pan-MRP inhibitor, led to a significant decrease in excreted G1 (maximal 59.1%) and G2 levels (maximal 42.4%), whereas Ko143 (5 and 20 μM), a selective BCRP inhibitor, caused moderate downregulation of excreted G1 (maximal 29.4%) and G2 (maximal 28.5%). Furthermore, MRP3 silencing resulted in a marked decrease of excretion rates (by 29.1% for G1 and by 21.1% for G2) and of fraction metabolized (fmet) (by 24.1% for G1 and by 18.6% for G2). Similar results, i.e., a significant reduction in excretion rates (by 34.8% for G1 and by 32.3% for G2) and in fmet (by 22.7% for G1 and by 23.1% for G2) were obtained when MRP4 was partially silenced. No obvious modifications in the excretion rates, intracellular levels, and fmet values of glucuronides were observed after short hairpin RNA (shRNA)-mediated silencing of transporters BCRP and MRP1. Taken together, our results indicate that MRP3 and MRP4 contribute more to the excretion of fraxetin-O-glucuronides than the other transporters do.